Sequential Kinase Inhibition (Idelalisib/Ibrutinib) Induces Clinical Remission in B-Cell Prolymphocytic Leukemia Harboring a 17p Deletion - H. Coelho; M. Badior; T. Melo (Case Reports in Hematology)
B-cell prolymphocytic leukemia (B-PLL) is a rare lymphoid neoplasm with an aggressive clinical course. Treatment strategies for B-PLL remain to be established, and, until recently, alemtuzumab was the only effective therapeutic option in patients harboring 17p deletions. Herein, we describe, for the first time, a case of B-cell prolymphocytic leukemia harboring a 17p deletion in a 48-year-old man that was successfully treated sequentially with idelalisib-rituximab/ibrutinib followed by allogeneic hematopoietic stem cell transplant (allo-HSCT). After 5 months of therapy with idelalisib-rituximab, clinical remission was achieved, but the development of severe diarrhea led to its discontinuation. Subsequently, the patient was treated for 2 months with ibrutinib and the quality of the response was maintained with no severe adverse effects reported. A reduced-intensity conditioning allo-HSCT from a HLA-matched unrelated donor was performed, and, thereafter, the patient has been in complete remission for 10 months now. In conclusion, given the poor prognosis of B-PLL and the lack of effective treatment modalities, the findings here suggest that both ibrutinib and idelalisib should be considered as upfront therapy of B-PLL and as a bridge to allo-HSCT.